A biomimetic synthesis-enabled stereochemical assignment of rhodotomentones A and B, two unusual caryophyllene-derived meroterpenoids from Rhodomyrtus tomentosa. Issue 20 (20th August 2021) - Deng, Lu-Ming; Hu, Li-Jun; Tang, Wei; Liu, Jia-Xin; Huang, Xiao-Jun; Li, Yue-Yue; Li, Yao-Lan; Ye, Wen-Cai; Wang, Ying
Abstract : Rhodotomentones A and B (1 and 2 ), two unusual caryophyllene-derived meroterpenoids (CDMTs) featuring a rare 6/6/9/4/6/6 hexacyclic ring system, along with their biogenetically-related CDMTs 7 and 12–15, were isolated from Rhodomyrtus tomentosa . Abstract : Rhodotomentones A and B (1 and 2 ), two unusual caryophyllene-derived meroterpenoids (CDMTs) featuring a rare 6/6/9/4/6/6 hexacyclic ring system, along with their biogenetically-related CDMTs 7 and 12–15, were isolated from Rhodomyrtus tomentosa . The planar structures of 1 and 2 were established by comprehensive spectroscopic data analyses. Based on their unique structural features, compounds 1 and 2 were hypothesized to be biosynthesized from three different building blocks. Inspired by two potentially biogenetic pathways, we completed the biosynthetic building block-based syntheses of 1 and 2, which enabled the unambiguous stereochemical assignment of 1 and 2 . In addition, three CDMTs 10, 14, and 17 exhibited potent in vitro antiviral activities against respiratory syncytial virus (RSV).